Agrarian transitions in rural Bushbuckridge, Mpumalanga province, South Africa: understanding dynamics and determinants - Rusere, F.; Mkuhlani, S.; Soropa, G.; Hunter, L.; Twine, W.; Samimi, C. (Frontiers Media, 2025)
In the coming decades, smallholder agriculture in the Global South will experience significant transformations due to environmental challenges, urbanization and demographic shifts. Although current research offers valuable perspectives on agrarian change, few studies have systematically tracked transitions in smallholder agriculture over time. Understanding long-term dynamics and integrating insights from diverse regions and sub-populations are essential for crafting effective and sustainable rural policies. This study employs a mixed-methods approach, combining quantitative longitudinal data from four time points (2010, 2014, 2019, and 2023) with qualitative insights from 10 villages within the Agincourt Health and Demographic Surveillance System site in Bushbuckridge, Mpumalanga Province, South Africa. Through both quantitative modeling and qualitative analysis, we explore agrarian trajectories, revealing trends, determinants, and transitions among various agrarian strategies. The findings emphasize the significant role of migrant and local off-farm employment in influencing the likelihood and level of subsistence farming, highlighting the dynamic nature of agrarian livelihoods. The impact of demographic factors, such as household size and gender, vary across different agrarian strategies. These insights offer valuable guidance for policy and intervention strategies aimed at enhancing rural livelihoods.